2013
DOI: 10.1113/jphysiol.2012.247981
|View full text |Cite
|
Sign up to set email alerts
|

Selective mitochondrial Ca2+ uptake deficit in disease endstage vulnerable motoneurons of the SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Key points• So far, increased excitability and calcium handling problems have been discussed as causes for motoneuron death in amyotrophic lateral sclerosis (ALS) mainly on the basis of studies in juvenile presymptomatic mice.• We developed a brainstem preparation to analyse excitability and calcium handling during disease progression up to disease endstage of motoneurons in an ALS mouse model. • Increased excitability of motoneurons is not seen at disease endstage, challenging this factor as a direct cause fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 71 publications
(95 reference statements)
1
65
0
1
Order By: Relevance
“…Knock-out or down-regulation of fission or fusion proteins reduces mitochondrial respiration and ATP generation (15). In addition, decreased mitochondrial calcium transport through the mitochondrial calcium uniporter (MCU) is observed in brainstem neurons of aging SOD1 G93A mice (16). Consistent with these findings, levels of stored mitochondrial calcium decline in these neurons (17).…”
Section: Amyotrophic Lateral Sclerosis and Mitochondrial Dysfunctionmentioning
confidence: 69%
“…Knock-out or down-regulation of fission or fusion proteins reduces mitochondrial respiration and ATP generation (15). In addition, decreased mitochondrial calcium transport through the mitochondrial calcium uniporter (MCU) is observed in brainstem neurons of aging SOD1 G93A mice (16). Consistent with these findings, levels of stored mitochondrial calcium decline in these neurons (17).…”
Section: Amyotrophic Lateral Sclerosis and Mitochondrial Dysfunctionmentioning
confidence: 69%
“…Although there is no consensus about the exact role of mitochondrial abnormalities [61], it is accepted that mitochondrial dysfunction is an important hallmark of ALS pathogenesis [5,62,63]. Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67]. Resveratrol improves mitochondrial function and induces biogenesis, although there is some controversy about whether this effect is mediated by AMPK activation [18] or by Sirt1 [16,68].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that calcium buffering capacity of mitochondria is affected in the brain and spinal cord of SOD1 G93A mice [127]. Furthermore, mitochondrial calcium uptake is also decreased in SOD1 G93A mice [128]. These disturbances of calcium buffering activity in motor neurons make them vulnerable to glutamatemediated excitotoxicity.…”
Section: Mitochondrial Dysfunction In Als and Therapeutic Strategiesmentioning
confidence: 95%